EDUKASI PENILAIAN STUNTING DAN STATUS GIZI BALITA PADA MASYARAKAT - Desiati Dese; Dewi Umi Fitriani; Dinda Indira Yanto; Siti Fatimah Thuzzahroh; Lia Kurniasari (JURNAL PENGABDIAN MANDIRI, 2022)
Stunting happens since the baby was still in the womb and early after the baby is born, but the stunting condition only appears after the child is 2 years old. The prevalence of infants under two years of age experiencing stunting in East Kalimantan is 29.2%, thus causing East Kalimantan to occupy the position of the province with the highest number of stunting cases with the seventeenth rank in Indonesia. The purpose of this activity is to increase the knowledge of mothers who have children under two on how to determine whether a child is in the stunting category and also determine the nutritional status of children. The method of carrying out activities was carried out through several stages, namely starting with identifying problems in the field, determining problem priorities, planning activities, and conducting evaluations. The results of the activity increased knowledge by 3% after being given education. Such activities need to be routinely carried out in the community to improve the health status of the community.